(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article analyzed peculiarities of development social and communicative skills of students as a leading mechanism for establishing partnerships. Outlined that affiliate interaction in the "student – student" system based on the relationships that provide equality of partners in the perception of each other, the orientation of subjects to the recognition of the value of the thoughts of everyone. Noted that successful formation of social and communicative skills possible provided in the educational process modeled organizational and pedagogical forms interpersonal interaction and communication. Outlined that organizational and pedagogical forms of interpersonal interaction through real experience and relevant activities of would encourage students to the detection of them social and communicative skills in daily life. Revealed that auditor and non- auditing activities must be a value-oriented character and makes on the basis of subject-subject partner interaction of participants in the educational process.